Successful overwintering of Aedes albopictus in Germany - Pluskota, Björn; Jöst, Artur; Augsten, Xenia; Stelzner, Lilith; Ferstl, Ina; Becker, Norbert (Parasitology research, 2016)
The Asian tiger mosquito (Aedes albopictus) is of great concern to public health authorities due to its vector competence and rapid spread across the globe. In 2015, two large local breeding populations of Ae. albopictus were discovered in southwest Germany. In spring 2016, we were able to demonstrate the first evidence of a successful overwintering in Germany of this originally tropical mosquito species in different research projects. Particularly noteworthy is the successful hatching of diapause eggs of an Italian strain (Calabria), which overwintered successfully in the field in St. Georgen im Schwarzwald (Baden-Wuerttemberg) at 820 m above sea level. Furthermore, within the scope of a larvae monitoring, the first larvae that hatched in the field were detected on the April 09, 2016 in a rain barrel within the Heidelberg population. Our first results show that self-extinction due to an unsuccessful overwintering cannot be assumed for populations of the Asian tiger mosquito which settled in Germany in previous years. The evidence of a successful overwintering of a large number of diapause eggs and the hatching of the first larvae in field conditions opens the control year against Ae. albopictus in southwest Germany.